Data-driven networking of global transcriptomics and male sexual development in the main malaria vector, Anopheles funestus - L. L. Koekemoer; M. Hajkazemian; J. W. Zawada; M. Mirzaie; Y. L. Dahan-Moss; S. N. Emami (Scientific Reports, 2023)
Abstract Deaths from malaria remain staggering despite global support that drives research into new territories. One major gap is our understanding of the sexual biological aspects of the male mosquito, which maintain the vector population solidity. Although Anopheles funestus s.s. is an extremely efficient African vector, little is known about the network between its sexual physiology and gene expression. The Culicidae male’s sexual maturity involves a suite of physiological changes, such as genitalia rotation that is necessary for successful mating to occur. We show that mating success is guided by genes and physiological plasticity. Transcriptome analysis between newly emerged males (immature) versus males with rotating genitalia (maturing) provides insight into possible molecular mechanisms regulating male sexual behaviour. Putative transcripts that were associated with male sexual maturation were identified and validated. The discovery of the functions of these transcripts could lead to identifying potential targets for innovative vector control interventions, and mosquito population suppression.